Predicting the young’s modulus of defect free radiata pine shooks in finger-jointing using resonance frequency - S.S, How; Williamson, C.J; Carradine, D.; Tan, Y.E; Cambridge, J.; Pang, S. (Maderas. Ciencia y Tecnología, 2025)
In this paper, dynamic MOE and static MOE of short-length radiata pine specimens produced for finger jointing were measured using non-destructive technique and correlated to each other. In order to obtain reliable static MOE data, 36 mm thickness shooks as well as the matched samples of reduced thickness (15mm) were tested, and the effect of annual growth rings on dynamic and static MOE is also addressed. Mathematical correlations were fitted between the dynamic MOE for the 36 mm thick shooks and the static MOE of the 15 mm thick samples. The coefficient of determination for dynamic MOE group 4,00-7,99 GPa was the strongest (R2 = 0,82) and the correlation strength was further improved for sorted quarter sawn samples (R2 = 0,92). Finally, the correlation between static modulus of rupture (MOR) and dynamic MOE is discussed.